High temperature electrochemical studies using a channel flow cell heated by radio frequency radiation - Moorcroft, M; Lawrence, N; Coles, B; Compton, R; Trevani, L (2001)
Systems involving one and two electron redox reactions were studied under hydrothermal conditions using a novel hydrodynamic method based on a conventional channel flow cell where the working electrode was heated by radio frequency radiation. The diffusion activation parameters obtained with the radio frequency channel cell were compared with independent data from microelectrode high temperature experiments and analysed in terms of the Stokes-Einstein equation. © 2001 Elsevier Science B.V.